1994
DOI: 10.1288/00005537-199403000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Oral and laryngeal muscle coordination during swallowing

Abstract: The objective of this experiment was to determine the relative contributions and patterns of activity of different muscles involved during the oral phase of swallowing. Electromyographic (EMG) signals were recorded from the orbicularis oris inferior, masseter, palatal elevator, anterior and posterior genioglossus, mylohyoid, anterior belly of the digastric, and vocalis muscles of 12 normal adult subjects. Each subject swallowed 15 mL of water, under normal and bite block conditions, 15 to 20 times. The integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 17 publications
6
38
0
Order By: Relevance
“…It is generally accepted that the swallowing re¯ex is controlled in the brainstem [1], However, if swallow mechanisms were controlled only at the brainstem level, we would expect to see little subject variability regarding amplitude and duration of the swallow muscles. The large subject variability in performing normal swallow and the Mendelsohn maneuver that was demonstrated by the results of this present study and previous studies [16,33] suggests that swallowing is a highly complex adaptive motor activity, which probably utilizes more than brainstem mechanisms. There are well-known cortical mechanisms important for swallowing such as the primary somatosensory cortex, premotor cortex, the primary motor cortex, and the anterior insula [34±38].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is generally accepted that the swallowing re¯ex is controlled in the brainstem [1], However, if swallow mechanisms were controlled only at the brainstem level, we would expect to see little subject variability regarding amplitude and duration of the swallow muscles. The large subject variability in performing normal swallow and the Mendelsohn maneuver that was demonstrated by the results of this present study and previous studies [16,33] suggests that swallowing is a highly complex adaptive motor activity, which probably utilizes more than brainstem mechanisms. There are well-known cortical mechanisms important for swallowing such as the primary somatosensory cortex, premotor cortex, the primary motor cortex, and the anterior insula [34±38].…”
Section: Discussionsupporting
confidence: 65%
“…Each individual subject may have a unique way of activating orofacial and strap muscles to perform normal swallow and the Mendelsohn maneuver. These results were con®rmed by Tallgren and Tryde [16] with two oral muscles and by Gay et al [33] with oral and pharyngeal muscles. It is generally accepted that the swallowing re¯ex is controlled in the brainstem [1], However, if swallow mechanisms were controlled only at the brainstem level, we would expect to see little subject variability regarding amplitude and duration of the swallow muscles.…”
Section: Discussionsupporting
confidence: 53%
“…These muscles have 2 principal roles in swallowing: the protection of the larynx by elevation, and the transportation of bolus by providing a secondary support to the tongue for its pumping action. 18,25,26 Therefore, the duration of the SM-EMG is a parameter that provides considerable information about the duration of the pharyngeal phase of swallowing that was prolonged in dysphagic patients with SBP with lacunar state. (4) The CP-EMG recordings made during swallowing revealed that the striated sphincter muscle of the upper esophageal sphincter was hyperreflexic and presumably dysinhibited like other brain stem reflexes, such as mandibular and palatopharyngeal reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, protective swallows can be initiated reflexively in response to the presence of the bolus either in the faucial pillars (Pommerenke, 1927) or in the pyriform sinuses (Pouderoux et al, 1996). Studies of the sequence of muscle activations in humans have demonstrated a series of activations progressing from jaw and perioral to suprahyoid, tongue, laryngeal and pharyngeal muscles during the swallowing pattern (Gay et al, 1994). Normal subjects vary in the particular sequence and timing of these muscle activations (Gay et al, 1994).…”
Section: Swallowingmentioning
confidence: 99%
“…Studies of the sequence of muscle activations in humans have demonstrated a series of activations progressing from jaw and perioral to suprahyoid, tongue, laryngeal and pharyngeal muscles during the swallowing pattern (Gay et al, 1994). Normal subjects vary in the particular sequence and timing of these muscle activations (Gay et al, 1994). This variability may depend on how the sensory input is altered by the bolus (Ertekin et al, 1997), differences in normal sensitivity (Pommerenke, 1927), and head position .…”
Section: Swallowingmentioning
confidence: 99%